Spherical indentation response of a Ni double gyroid nanolattice - Prusty, R. K. (2022)
The effect of indentation strain εi upon hardness H and elastic modulus E of a Ni Double Gyroid (DG) nanolattice was investigated using a spherically-tipped nanoindenter. H remains invariant, while E decreases linearly, with increasing εi. Results reveal the progressive collapse of the DG lattice beneath the indenter. The measured values of H and extrapolated value of E at εi = 0 were used to estimate the yield strength and elastic modulus of the Ni cell walls. The latter was compared with the ideal strength of Ni, nanocrystalline films and of sub-100 nm diameter single crystals.